Misuse of foreign diplomatic passports - Deckert, A (Queensland University of Technology, 2011)
A number of internet consultancies advertise their highly-priced intermediary services for obtaining a genuine diplomatic passport. Clients are promised increased status, tax relief, and diplomatic immunity. Under the Vienna Convention on Diplomatic Relations 1961, diplomatic immunity – meaning exemption from lawsuits and prosecution – shall be granted to accredited diplomats only; however several real-life examples prove that genuine diplomatic passports can be obtained from a number of African and Pacific countries and are being used to claim diplomatic immunity even though passport holders have not been officially accredited as diplomats in a host country. This paper firstly describes how a genuine diplomatic passport is obtained, despite the passport holder’s lack of accreditation. Secondly, it analyses the evidentiary value such a passport holds under international diplomatic law, especially in regards to proving the passport holder’s right to claim diplomatic immunity. It explores how Article 40 of the Vienna Convention on Diplomatic Relations 1961 enables ‘fake diplomats’ to successfully claim diplomatic immunity, and whether the misuse of genuine diplomatic passports constitutes a new form of white-collar crime.
Keywords: Courts; Eco-justice; Environmental crimes; Global justice; Governance and ethics; Human rights; Indigenous justice; Penal policy; Policing; Sex and gender; Social justice